BAD: Body – Art – Digital technology - Skregelid, Lisbet (Nordic Journal of Art & Research, 2024)
During the first lockdown in March 2020, I started running two to three times a week to a nearby beach. Since then, I have stopped each time about halfway, and have been filming the sea view from the same spot for 30 seconds with my mobile phone. The now over 550 films (October 2024) are stored on the digital platform Padlet that makes it possible to share with others. The project My stunning stream - Made with a little mischief (Skregelid, 2020-) makes use of a/r/tography which is a practice-based methodological approach that unites art, education, and research. A/r/tography explores art, research and education as forms of performative, explorative and lived inquiry, and thereby stretches the boundaries between these domains. This article draws attention to how the body and digital technology are entangled and interwoven in this project, and how this affective connectedness offers potentials for enabling ecological awareness in educational settings. It makes use of theories that consider bodies and technologies as united intra-actions and that are concerned with how to live your life in the world. Photo: Libeth Skregelid